1999
DOI: 10.1002/hep.510290203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Losartan, An Angiotensin Ii Receptor Antagonist, on Portal Pressure in Cirrhosis

Abstract: The primary objective of drug therapy in portal hypertension is the prevention of variceal bleeding. The use of nonselective ␤-blockers that reduce portal pressure by lowering splanchnic blood inflow 1 has proved effective in this indication. Treatment with propranolol or nadolol reduces the risk of first hemorrhage 2 as well as that of further bleeding episodes in patients with a history of variceal bleeding. 3 However, the average reduction in portal pressure by 15% achieved with ␤-blockers is moderate, 4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(132 citation statements)
references
References 35 publications
2
121
0
2
Order By: Relevance
“…In rats, experimental models of liver fibrosis induced by bile duct ligation or carbon tetrachloride or choline deficiency, administration of irbesartan, olmesartan, telmisartan, candesartan, or losartan inhibited expression of collagens and TGFb in stellate cells and reduced established liver fibrosis (Kurikawa et al, 2003;Ueki et al, 2006;Hirose et al, 2007;Yoshiji et al, 2009;Moreno et al, 2010;Kato et al, 2012). In clinical practice, however, the usefulness of treating liver fibrosis with ARBs remains contradictory (Schneider et al, 1999;Gonzalez-Abraldes et al, 2001;Lee, 2014). A handful of randomized controlled trials suggest that ARB treatment is a potentially useful therapeutic approach in patients with nonalcoholic fatty liver disease (Paschos and Tziomalos, 2012).…”
Section: G Pathophysiological Aspects Of Angii Type 1 Receptor Activmentioning
confidence: 99%
“…In rats, experimental models of liver fibrosis induced by bile duct ligation or carbon tetrachloride or choline deficiency, administration of irbesartan, olmesartan, telmisartan, candesartan, or losartan inhibited expression of collagens and TGFb in stellate cells and reduced established liver fibrosis (Kurikawa et al, 2003;Ueki et al, 2006;Hirose et al, 2007;Yoshiji et al, 2009;Moreno et al, 2010;Kato et al, 2012). In clinical practice, however, the usefulness of treating liver fibrosis with ARBs remains contradictory (Schneider et al, 1999;Gonzalez-Abraldes et al, 2001;Lee, 2014). A handful of randomized controlled trials suggest that ARB treatment is a potentially useful therapeutic approach in patients with nonalcoholic fatty liver disease (Paschos and Tziomalos, 2012).…”
Section: G Pathophysiological Aspects Of Angii Type 1 Receptor Activmentioning
confidence: 99%
“…Captopril, an ACE inhibitor, has been well studied and reported to suppress rat hepatic fibrosis induced by pig serum (Ohishi et al, 2001). Similarly, angiotensin receptor 1 antagonists reduce the portal pressure in hepatic cirrhosis (Schneider et al, 1999). The transforming growth factor-β (TGF-β ) plays a dominant role in the development of fibrosis (Muriel, 2007b) and this factor may be enhanced by AT-II (Jonsson et al, 2001).…”
Section: Captopril and Liver Fibrosismentioning
confidence: 99%
“…Given data indicating that angiotensin II induces stellate cell (and smooth muscle cell) contractility, the RAAS is an attractive therapeutic target in intrahepatic portal hypertension. However, studies in humans with cirrhosis in which angiotensin II signaling has been blocked have been met with mixed results [83][84][85] ; in particular, angiotensin II receptor antagonists adversely affected glomerular filtration rate and caused systemic hypotension in cirrhotic patients 85 ; therefore, caution is required with these agents. Indeed, because of potential systemic adverse effects, some have suggested that cirrhotic patients not be treated with these compounds.…”
Section: Rockey Hepatology January 2003mentioning
confidence: 99%